2021
DOI: 10.1108/lodj-08-2020-0342
|View full text |Cite
|
Sign up to set email alerts
|

When and how authoritarian leadership influences employee innovation behavior in the context of Chinese culture

Abstract: PurposeThis paper aims to explore the mechanism and boundary conditions of authoritarian leadership that influence employee innovation behavior (EIB) in Chinese culture based on the leader–member exchange theory and state–trait theory.Design/methodology/approachThe authors used Mplus and SPSS to test the proposed model with data from 286 leader–employee dyads in Chinese companies. In this study, questionnaires were collected through commission and field investigation.FindingsThe results indicate that authorita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Among multiple business process resources, employees' innovative work behavior (IWB) has emerged as a substantive factor (Kumar et al, 2022 ). Although, in the current study, antiquities have established the positively significant relationship of IWB with leadership (Kim and Koo, 2017 ), work climate (Baradarani and Kilic, 2018 ), OI (Luhgiatno and Dwiatmadja, 2020 ), PIS (Zhang et al, 2021 ), and proactive personality (PP) (Ahmad et al, 2021b ; Zhang et al, 2021 ). PP is essential for individual and organizational success.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Among multiple business process resources, employees' innovative work behavior (IWB) has emerged as a substantive factor (Kumar et al, 2022 ). Although, in the current study, antiquities have established the positively significant relationship of IWB with leadership (Kim and Koo, 2017 ), work climate (Baradarani and Kilic, 2018 ), OI (Luhgiatno and Dwiatmadja, 2020 ), PIS (Zhang et al, 2021 ), and proactive personality (PP) (Ahmad et al, 2021b ; Zhang et al, 2021 ). PP is essential for individual and organizational success.…”
Section: Introductionmentioning
confidence: 57%
“…The employees of the IT industry in China could enhance the business growth by triggering the IWB through the PP. In many studies, Truxillo et al ( 2012 ); Ruiz Moreno et al ( 2021 ); and Zhang et al ( 2021 ) have conceptualized and accepted that PP positively impacts employee outcomes but ignored the IWB, so this study aimed to fill a vital literature gap. Unfortunately, the employees in the IT sector are missing PP's features, which is the fundamental reason they are unable to meet the standards of innovative products; resultantly, our competitors are cashing the scenario, from here the Schumpeter's theory of innovation luminous the path.…”
Section: Introductionmentioning
confidence: 99%
“…We referred to the method of testing the moderating effect in the research of Au et al (2017) and Zhang et al (2021a) to test H6a and H6B. First, local and cross-border knowledge search were introduced as dependent variables into M15 and M19, and control variables were introduced at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…When the level of authoritarian leadership is low, it will promote creative deviance, and when the level of authoritarian leadership is high, it will inhibit creative deviance behavior. Zhang et al ( 2021 ) found that authoritarian leadership can positively influence employee innovation behavior within a certain range. To sum up, authoritarian-benevolent leadership must be highly related to employees' innovative behavior, but at present, there is little research on the influence of this kind of ambidextrous leadership, which is widely present in Chinese organizational management, on the innovative behavior of employees.…”
Section: Theory and Modelmentioning
confidence: 99%